2006
DOI: 10.1002/bip.20622
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of DNA binding determined in optical tweezers experiments

Abstract: The last decade has seen rapid development in single molecule manipulation of RNA and DNA. Measuring the response force for a particular manipulation has allowed the free energies of various nucleic acid structures and configurations to be determined. Optical tweezers represent a class of single molecule experiments that allows the energies and structural dynamics of DNA to be probed up to and beyond the transition from the double helix to its melted single strands. These experiments are capable of high force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 148 publications
(179 reference statements)
6
93
0
Order By: Relevance
“…In these cells, chromosomal DNA is packed in a hierarchical structure. At the lowest level in the hierarchy (and our prime concern here), DNA is wrapped in 147 base pair segments roughly 1 3 4 times around a protein complex (the histone octamer) to form a structure known as the nucleosome as shown in Figure 4.…”
Section: Dna Packing In Eukaryotesmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cells, chromosomal DNA is packed in a hierarchical structure. At the lowest level in the hierarchy (and our prime concern here), DNA is wrapped in 147 base pair segments roughly 1 3 4 times around a protein complex (the histone octamer) to form a structure known as the nucleosome as shown in Figure 4.…”
Section: Dna Packing In Eukaryotesmentioning
confidence: 99%
“…Scales larger than the persistence length are typical of those that DNA assumes in most in vitro molecular biology experiments such as singlemolecule DNA pulling experiments. 2,3 DNA bending has been exhaustively studied in this regime. When DNA is bent on a scale shorter than p , we refer to it as tightly bent, implying that the energy cost to effect such bending is large compared to k B T. Interestingly, in many of the most important biological processes, DNA adopts tightly bent configurations.…”
mentioning
confidence: 99%
“…[30][31][32] To elucidate mechanical properties, optically trapped or magnetically responsive beads can be conjugated to a single DNA strand, enabling controlled stretching and twisting of the molecule. [33][34][35][36] By fixing one end of a fluorescently labeled DNA strand in an elongational flow, it is also possible to observe inhomogenous hydrodynamic stretching, which is a theoretically interesting phenomenon. [36][37][38] A single DNA strand may be visualized as it interacts with pillars in a microfluidic slit, [39][40][41] or as it escapes from a deep well into a thin slit, and it is hoped that the knowledge gained from such studies will lead to faster methods of lab-on-chip DNA sorting.…”
Section: Nanofluidic Structures For Directly Altering the State Of Tamentioning
confidence: 99%
“…Measurements of the transition free energy associated with overstretching under a variety of biochemical conditions are consistent with DNA denaturation and unwinding, possibly indicating a melting transition of double-stranded to singlestranded DNA. 55,56 Alternatively, it has been suggested that overstretched DNA adopts a conformation with a distinct base-paired structure. 53,54 …”
Section: Elastic Properties Of Dnamentioning
confidence: 99%
“…A characterization of the dependence of the gp32 equilibrium binding constant on the ionic strength revealed that protein binding is regulated by intramolecular conformational changes (For more information, see the review by McCauley and Williams in this issue). 55 …”
Section: Dna Denaturation By Single-stranded Dna Binding Proteinsmentioning
confidence: 99%